A crise do subprime e seus efeitos sobre os Estados Unidos e reflexos no Brasil - Campos, Catherine Fernandes de [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Between December 2007 and June 2009 the United States witnessed 18 months of recession that became known as the subprime crisis. Beginning in the housing market, the crisis moved into the banking and financial markets and spread throughout the entire economy through a domino effect, affecting the majority of other businesses. A major reflection of this was the large rise in unemployment rates due to business slashing jobs in an attempt to preserve cash. Although the crisis has officially ended, the unemployment rate reached over 10% in 2010 in the United States. American's continue to seek new jobs in a very difficult employment market, while attempting to manage the family household budget. American household income, which decreased either by pay cuts, job loss, and the effects of inflation, leads the majority of Americans to declare that the crisis had not yet ended. The crisis has spread to the world in varying degrees. Brazil was one of the countries least affected due to government policies and the large amount of foreign exchange. Although the crisis has affected Brazil only slightly, we will show how it reached this country and how the government solved this problem. This research paper will explain how the subprime crisis began, how it manifested itself in the U.S. economy and throughout the population. Also, it will show the crisis’ effects in Brazil and show some statements from Americans with their respective views and their experiences relative to the crisis

Entre dezembro de 2007 e junho de 2009 os Estados Unidos presenciaram 18 meses de recessão que ficaram conhecidos como a crise do Subprime. Iniciada no mercado imobiliário, a crise passou para o mercado bancário e financeiro e se alastrou para toda a economia através de um efeito dominó, atingindo diversas outras empresas de alguma maneira e refletindo-se em altos índices de desemprego. Mesmo a crise tendo oficialmente acabado, os índices de desemprego chegaram a 10% em 2010 nos Estados Unidos. Enquanto muitas pessoas procuram um novo emprego, outras tentam administrar a renda familiar que diminuiu, seja por cortes nos salários ou não aumento dos mesmos, e pela inflação que cresceu no último ano, o que leva a população a declarar que a crise ainda não teve seu fim. A crise se alastrou para o mundo em intensidade diferente. O Brasil foi um dos países que menos sofreu devido às políticas do Governo e a grande quantidade de divisas. Apesar de a crise ter se refletido suavemente no Brasil mostraremos as formas como ela atingiu esse país e mostraremos como o governo resolveu esse problema. Essa monografia explicará como a crise do Subprime se iniciou, como ela se refletiu na economia norte-americana e por fim, na população. Falará ainda dos reflexos da crise no Brasil e mostrará alguns depoimentos de norte-americanos com suas respectivas visões e experiências sobre a crise
Keywords: Economia; Crise financeira global, 2008-2009; Recessão (Economia) - Estados Unidos; Subprime mortgage crisis; American recession; 2008 Financing crisis